1986
DOI: 10.1021/ic00239a011
|View full text |Cite
|
Sign up to set email alerts
|

Electron-transfer reactions of technetium complexes. 1. Rate of the self-exchange reaction of the technetium(I)/technetium(II) couple [Tc(DMPE)3]+/2+, where DMPE = 1,2-bis(dimethylphosphino)ethane

Abstract: Br), prepared anaerobically in perchloric acid at 0.10 M ionic strength, was saturated with alkali-scrubbed nitric oxide. A solution of chromium(ll) perchlorate was then slowly added while the solution was efficiently stirred and continuously saturated with NO. After addition of Cr2+ was complete, the NO was removed with a vigorous stream of argon. Samples were taken for the analysis of the cobalt(II) produced by the thiocyanate method57 in 1:1 aqueous acetone. This measurement was made by incorporating an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that non-aqueous [Tc(dmpe) 3 ] + is part of a redox couple with well-defined, reversible electrochemistry. It can be reversibly converted to the higher oxidation state [Tc(dmpe) 3 ] 2 + according to the process below, with a formal reduction potential of 0.05 V vs. Ag/AgCl: ( Doyle et al 1986, Chatterjee et al 2011b …”
Section: Tc(ii) Tris-phosphine Complexes and Congenersmentioning
confidence: 99%
“…Previous studies have shown that non-aqueous [Tc(dmpe) 3 ] + is part of a redox couple with well-defined, reversible electrochemistry. It can be reversibly converted to the higher oxidation state [Tc(dmpe) 3 ] 2 + according to the process below, with a formal reduction potential of 0.05 V vs. Ag/AgCl: ( Doyle et al 1986, Chatterjee et al 2011b …”
Section: Tc(ii) Tris-phosphine Complexes and Congenersmentioning
confidence: 99%
“…If pentane-2,4-dione is used as a ligand, the red Tc(III) complex, [Tc(acac) 3 ], results (48), while the Nsubstituted pyridinone ligands form very stable trisligand Tc(IV) complexes [Tc(L) 3 ] + (L ) N-substituted pyridinonate) (49). If the ligand contains P donors, Tc(IV), Tc(III), and Tc(I) complexes are isolated depending on the number of P donors and coligands in the complex (50)(51)(52). Isonitrile ligands form colorless Tc(I) complexes, [(Tc(CNR) 6 ] + , almost quantitatively (53).…”
Section: Requirements For New 99m Tc-based Radiopharmaceuticalsmentioning
confidence: 99%
“…Moreover, the fe 22 values for the self-exchange reactions of the TC(DMPE)3 +/2+ and Re(DMPE)3 +/2+ are well established from both the measured rates of cross reactions [3,4] and calculations based on structural data [4], Thus, the Marcus formulation can be used to calculate the fen values for the Np(VI)/(V) and Pu(VI)/(V) self-exchange reactions from values of the Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/18/15 11:16 PM equilibrium constants (Table 1), the measured rate constants for the cross reactions (k 12 ), and the selfexchange rates of M(DMPE)3 +/2 + . When the self-exchange rate constant for the Tc(DMPE)3 +/2+ couple and the measured rate (k l2 ) for the cross-reaction are used, the values for fcn are 0.69 and 3.0 M _1 s _1 for Np(VI)/(V) and Pu(VI)/(V) respectively; whereas, when the k 12 for the Re(DMPE)3 +/2+ couple is used, the ku values are 0.64 and 8.9 M _1 s _1 , respectively.…”
Section: D[t^(ii)] = Fe/[tc(i)][pu(vi)] + Fe R [Tc(ii)][pu(vi)] DI (3)mentioning
confidence: 57%
“…The extension of these studies to actinide redox reactions in basic carbonate solutions attains additional relevance by the need for a greater understanding of actinide chemistry under environmental conditions. Previous kinetic studies involving actinide complexes have included investigations of electron exchange and oxo-group transfer reactions, and the in- [3,4] have recently been determined. These M(II)/(I) couples provide useful electron transfer partners since the M(I) form is colorless while the M(II) form has a relatively intense band in the visible region which can be readily monitored.…”
Section: Introductionmentioning
confidence: 99%